Malaysian plover occurrence in relation to crustacean prey abundance at Tanjung Resang Beach, Mersing, Johor - Lim, Yeong Shya (2019)
Sandy beach is an important ecosystem for most coastal and intertidal animals especially for the waders and crustaceans such as crabs. The aim for this study was to identify the species of sand bubbler crabs and to compare the crustacean prey abundance in relation to anthropogenic disturbance level, existence and breeding condition of the Malaysian Plovers. This study was conducted from 6th July to 8th July 2018 in Tanjung Resang beach, Mersing, Johor. In overall, 15 sampling points were set along a transect on the beach. The abundance of crabs was estimated by counting the number of crab burrows within one meter square quadrats. Results showed that the species of sand bubbler crabs found on the beach was most likely Dotilla wichmanni. Kruskal-Wallis H test indicated that there was a highly significant difference in the number of crab burrows at different sampling points. A Mann-Whitney U test showed that different anthropogenic disturbance level did affect the number of crab burrows at different points. The points with presence and absence of the Malaysian Plovers had also significant difference in the crab burrow density. However, the Mann-Whitney U test found that the points with breeding-pairs and non-breeding individuals of the plovers had no significant difference in the number of crab burrows. Tourism development and anthropogenic disturbance may affect the crab survival ability and in turn altered the occurrence and feeding behaviour of the Malaysian Plovers.